Stent-Assisted Coiling of Cerebral Aneurysms: A Multicenter Analysis. (1st September 2019) - Mokin, Maxim; Primiani, Christopher T; Piper, Keaton; Fiorella, David; Rai, Ansaar; Orlov, Kirill; Kislitsin, Dmitry; Gorbatykh, Anton; Mocco, J D; DeLeacy, Reade; Lee, Joyce; Spiotta, Alejandro M; et al.
Abstract: INTRODUCTION: New devices have allowed endovascular stent-assisted coiling for the treatment of cerebral aneurysms. It remains unknown how each type of stent affects the safety, efficacy, and clinical outcomes of the stent-coiling procedure. METHODS: This study compared the outcomes of endovascular coiling of cerebral aneurysms using Neuroform (NEU), Enterprise (EP), and Low-profile Vi_sualized Intraluminal Support (LVIS) stents. Cases of aneurysms treated with more than one type of stents (NEU, EP, LVIS) used for coiling of the same lesion (n = 24) or other devices (n = 32) were excluded. Patient characteristics, angiographic results using the Raymond-Roy grade scale (RRGS), clinical outcomes and procedural complications were analyzed in our study. Patients data was retrospectively collected from 6 academic centers. RESULTS: A total of 659 patients with 670 cerebral aneurysms treated with stent-assisted coiling (NEU, n = 182; EP, n = 158; LVIS, n = 330) were included in final analysis. Patient characteristics included mean age 56 ? 12 yr old, female prevalence 74% and aneurysm rupture on initial presentation of 19%. The degree of occlusion at baseline angiography was significantly associated with age ( P = .002), location by circulation ( P = .002), aneurysm size ( P = .009), and rupture status ( P = .013). We found differences in complete occlusion on baseline imaging, defined as RRGS I, among the three stents: LVIS 64% (210/326); NEU 56% (95/169); EP 48% (68/143); P = .008. The difference of complete occlusion on 10.5 mo (mean) and 8 mo (median) angiographic follow-up was also significant: LVIS 84% (251/299); NEU 78% (117/150); EP 67% (83/123); P = .004. There were 7% (47/670) intraprocedural complications and 11.5% (73/632) postprocedural related complications in our cohort. CONCLUSION: There were significant affects based on type of stent used for assisted coiling in the immediate and long-term angiographic outcomes in our cohort. Randomized prospective trials are warranted to compare stent types and clinical outcome.